(3ebOeI aj GdbjGS GdGbJUGOjs - (3GehQj gGOj(B, (3cGXes ((3YeGf(B:s (3OGQ GdRgQGf(B,s, 2009)
(3GdfehPL GdNWj GdHSjW h GdfehPL GdNWj GdYGe , eTcdI YOe JLGfS GdJHGjf h eTcdI GdEQJHGW GdPGJj , eTcdI GdJYOO GdNWj , GdbjhO GdeJWGHbI h efXheI GdeYGOdGJ GdBfjI eY hLhO CSFdI YGeI eMdhdIs
(3LOGhd GMUGFjI U(B.345(3, eUGOQ U(B.355s
Keywords: (3GdEMUGA (B- (3GdeYGedGJ GdEQJHGWjI s; (3GdEbJUGO GdbjGSjs; (3GdGbJUGOs